Theoretical approach to a contemporary educational geography, politics and communication (Encuentros, 2016)
This article of bibliographical review tries to explore the concepts and contemporary notions about an educational, political and communicative field. It is explained that the formation of a person in general acquires new senses and that the current society citizen is that one who through the securing, production and creation of knowledge, is capable of recognizing the contexts where he is able to co-construct his significance and his performance. This research demonstrates that the transformations in the educational, political, and communicative ambiances are long lasting, and they are not induced by conscience, or by the speech of conscience, but it would be necessary to generate a few conditions of material and cultural reproduction by the individuals, which would involve in the institutions, transformations, in the interaction of the same ones, as political actors and according to the subjects that compose them, generating innumerable expectations, which might not be all tackled in this article given the magnitude of its range. For this reason, this research tries to articulate the Humanist vision of education, politics, and communication, as sciences, disciplines or fields of study, from a qualitative and theoretical - conceptual perspective. The research methodology is faced from the critical - social theory, as emergent theory, which allows to open the debate incorporating contemporary points of view and in context with reality, tackling the theoretical and extra-theoretical interests that arise in the process. The challenge we face involves a complex look to many fields of knowledge transversely, from human sciences to social sciences, in the opening to the comprehension of new rationalities and new cartographies, and perhaps, new ways of thinking considering transdisciplinarity.Keywords: Education, Politics, Communication, Education policy.